2015
DOI: 10.1186/s12894-015-0070-1
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic outcomes in men with metastasis to the prostatic anterior fat pad lymph nodes: a multi-institution international study

Abstract: BackgroundThe presence of lymph nodes (LN) within the prostatic anterior fat pad (PAFP) has been reported in several recent reports. These PAFP LNs rarely harbor metastatic disease, and the characteristics of patients with PAFP LN metastasis are not well-described in the literature. Our previous study suggested that metastatic disease to the PAFP LN was associated with less severe oncologic outcomes than those that involve the pelvic lymph node (PLN). Therefore, the objective of this study is to assess the onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…OH KWANG KWON 1* , YUN-SOK HA 2* , ANN-YAE NA 1 , SO YOUNG CHUN 3 , TAE GYUN KWON 2,3 , JUN NYUNG LEE 2# and SANGKYU LEE 1# expression of tumor proteins, which might be used to indicate metastatic PCa. In particular, tissue-based biomarkers can be used as diagnostic, prognostic, and predictive markers (6).…”
Section: Identification Of Novel Prognosis and Prediction Markers In mentioning
confidence: 99%
“…OH KWANG KWON 1* , YUN-SOK HA 2* , ANN-YAE NA 1 , SO YOUNG CHUN 3 , TAE GYUN KWON 2,3 , JUN NYUNG LEE 2# and SANGKYU LEE 1# expression of tumor proteins, which might be used to indicate metastatic PCa. In particular, tissue-based biomarkers can be used as diagnostic, prognostic, and predictive markers (6).…”
Section: Identification Of Novel Prognosis and Prediction Markers In mentioning
confidence: 99%
“…They also demonstrated that the PAFP contains lymph nodes and may be upstaged because of positive prostate cancer metastases 8 . Recently, several studies have demonstrated 9%-17% of PAFPs to contain lymph nodes (Table 6 ) 8 - 16 , 18 .…”
Section: Discussionmentioning
confidence: 99%
“…In our series, PAFP lymph nodes were found in few patients; however, 14.5% (11 of 76) of the patients harbored malignancy in PAFP lymph nodes compared with 6.8% (58 of 849) of the patients harboring metastases in pelvic lymph nodes. In published series, the rate of metastatic prostate cancer in PAFP lymph nodes ranges from 0.6% to 2.5% (Table 6 ) 8 - 16 , 18 . Two studies have included patients undergoing open radical retropubic prostatectomy (RRP).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation